Origin of ligand effects on reactivities of pincer-Pd catalyzed hydrocarboxylation of allenes and alkenes with formate salts: a computational study. Issue 11 (15th May 2018) - Lv, Xiangying; Huang, Fang; Wu, Yan-Bo; Lu, Gang
Abstract : Distortion induced by R substituents on PGeP -pincer ligands is the key factor affecting the reactivity of CO2 insertion into allylpalladium and benzylpalladium intermediates. Abstract : The origin of ligand effects on pincer-Pd catalyzed hydrocarboxylation of allenes and alkenes was investigated using density functional theory (DFT) calculations. The computations reveal that the CO2 insertion into allylpalladium and benzylpalladium intermediates is the rate-determining step for both allene and alkene substrates. Distortion/interaction analysis indicates that CO2 insertion into the benzylpalladium intermediate via a 3-membered transition state has larger distortion energy than that of CO2 reacting with the allylpalladium intermediate through a 6-membered transition state. The linear relationships between the distortion energy and the activation energy are applicable for a series of PGeP -pincer ligands with different P -bound R substituents.